2007
DOI: 10.1158/0008-5472.can-06-3350
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase Cε, which Sensitizes Skin to Sun's UV Radiation–Induced Cutaneous Damage and Development of Squamous Cell Carcinomas, Associates with Stat3

Abstract: Chronic exposure to UV radiation (UVR) is the major etiologic factor in the development of human skin cancers including squamous cell carcinoma (SCC). We have shown that protein kinase CE (PKCE), a Ca 2+ -independent, phospholipiddependent serine/threonine kinase, is an endogenous photosensitizer. PKCE is among the six isoforms (A, D, E, H, M, and Z) expressed in both mouse and human skin. PKCE transgenic mice, which overexpress PKCE in the basal epidermal cells and cells of the hair follicle, are highly sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 46 publications
6
87
0
Order By: Relevance
“…However, our data were unable to characterize the direct interaction of ERK1/2 with STAT3 ( Figure 6). Next, we suggested that ePKC could directly phosphorylate STAT3 at the serine residue in neurons, as a direct interaction between ePKC and STAT3 phosphorylation at serine 727 residue has been shown in cancer cells (Aziz et al, 2007). However, we could not detect the direct interaction of ePKC with STAT3 ( Figure 6).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…However, our data were unable to characterize the direct interaction of ERK1/2 with STAT3 ( Figure 6). Next, we suggested that ePKC could directly phosphorylate STAT3 at the serine residue in neurons, as a direct interaction between ePKC and STAT3 phosphorylation at serine 727 residue has been shown in cancer cells (Aziz et al, 2007). However, we could not detect the direct interaction of ePKC with STAT3 ( Figure 6).…”
Section: Discussionmentioning
confidence: 74%
“…The STAT3-specific inhibitor used in this study was the SH 2 domain-binding peptide, which interferes with phosphorylation of the tyrosine residue, and disrupts STAT3 dimerization and STAT3 activity in vitro (Turkson et al, 2001). As mentioned earlier, complete activation of STAT3 requires phosphorylation at both tyrosine and serine residues (Aziz et al, 2007;Li and Shaw, 2004). In this context, these results led us to conjecture that the STAT3 inhibitory peptide prevented the complete activation process of STAT3 transcriptional activity and then inhibited STAT3-mediated COX-2 expression after PC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKC isoforms expressed in keratinocytes may contribute to these changes. STAT3 has been shown to be phosphorylated at Ser727 residues by PKCε, and PKCε transgenic mice demonstrate phosphorylation of both Ser727 and Tyr705 residues and therefore display fully activated STAT3 (41). Keratinocyte-specific overexpression of PKCα in mice results in expression of TNF-α and VEGF and epidermal neutrophilic inflammation (42,43), i.e., characteristic features of psoriasis.…”
Section: Figurementioning
confidence: 99%
“…Transgenic overexpression of PKCe in the skin drives the development of squamous cell carcinoma and a metastatic phenotype, and it predisposes mice to skin cancer in response to UVR exposure (11,12). There is a significant reduction of prostate cancer growth in TRAMP mice with PKCe-deficient background (13).…”
Section: Discussionmentioning
confidence: 99%